Examining Applicability of RSQS with Added Dimensions for Organized Apparel Retailers in India: Validation and Development of Scale. Issue 1 (June 2017) - Hasan, Arif
This study endeavours to validate and develop a scale for organized apparel retail stores, as there is a need to develop and validate a modified instrument. Primary data have been collected from selected organized apparel retailers. Statistical tools, exploratory factor analysis (EFA) and structural equation modeling (SEM), were applied. It revealed that Retail Service Quality Scale (RSQS) model in original form is deficient and less appropriate in the Indian context, modified scale (i.e., Apparel Store Service & Product Quality Scale [ASSPQS]) may exhibit strong model fit for apparel retail sector. The findings and recommendations will enable retail stores to gather insights into current levels of service and product quality and may facilitate them in the improvement of certain aspects in service and product quality of the stores.